INTERACTIVE COMMUNICATION WITH EDMODO IN EFL CLASSROOM - Yuliana Ningsih,; Wan Yuliyanti, (JEE (Journal of English Education), 2021)
Virtual learning is very much important in the 21st century in increasing interest in communicating in EFL classrooms. Edmodo is one of the media used for virtual learning. This research primarily aimed at describing interactive communication and students’ perspective of the online media "Edmodo" as a means of learning the EFL Classroom. The method used is qualitative methods with data collection techniques with documentation techniques, and observation techniques. Students’ perspective were collected by interviews. Besides that advantages of Edmodo and description classroom activities observed. The results of the analysis showed that Edmodo can be used as an effective learning medium. Edmodo, as a learning tool, can also be an easier introduction to students so that English knowledge be interested to communicate globally. Moreover, it revealed that using Edmodo had positive perspective from students towards interactive communication.